Pengembangan Storytelling Desa Wisata melalui Pementasan Drama dan Event Budaya Umbul Sidomulyo 2025 - Hermawan, Hary; Prihatno; Afif, Fuadi; Hermawan, Budi; Sinangjoyo, Nikasius Jonet; Saputra, Arif Dwi; Islami, Mona Erythrea Nur; Mahiswara, Amelia Lintang; Widianingrum, Retno Moortrisari; Anwari, Hamdan; Damasdino, Fian; Cahyani, Andhira; Meilinda, Yuanita (Jurnal Abdimas Pariwisata, 2026)
Development of Tourism Village Storytelling through Drama Performances and the Umbul Sidomulyo Cultural Event 2025. This Community Service Program (PKM) aims to develop and disseminate storytelling techniques in Umbul Sidomulyo Tourism Village through drama performances and the Umbul Sidomulyo Cultural Event 2025. Storytelling was selected as an effective tourism communication medium to enhance visitor experiences and strengthen the cultural identity of the tourism village. The implementation methods included material preparation, training for tourism stakeholders, implementation during the cultural event, and evaluation. The results demonstrate improvements in guides’ skills in delivering tourism narratives, strong community enthusiasm, and increased tourist visitation interest. This program contributes to strengthening the competitiveness of Umbul Sidomulyo Tourism Village as a destination based on cultural values and local narratives.